2012
DOI: 10.1038/bmt.2012.55
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cytogenetics risk on outcome after reduced intensity conditioning allo-SCT from an HLA-identical sibling for patients with AML in first CR: a report from the acute leukemia working party of EBMT

Abstract: ,10 for the ALWP of EBMT So far the impact of cytogenetics risk on outcome in the context of reduced intensity conditioning (RIC) allo-SCT has been poorly studied. We have identified 378 AML patients in first CR who underwent RIC allo-SCT from an HLA-matched sibling donor between 2000 and 2007 reported to the European Group for Bone and Marrow Transplantation and for whom detailed cytogenetics data were available (good risk: n ¼ 21; intermediate risk: n ¼ 304; and poor risk: n ¼ 53). With a median follow-up of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 24 publications
3
14
1
Order By: Relevance
“…This study also identified poor risk cytogenetics, being in second versus in first CR, and conditioning with low-dose TBI-based RIC as being associated with worse LFS or OS, confirming previous reports. 18,31,32 Finally, our study demonstrated higher mortality in patients above 56 years of age at transplantation in comparison with younger patients, in contrast to what has been observed in a recent report from the CIBMTR analyzing data from 545 patients with AML given RIC allo-SCT, 18 perhaps because analyses were not adjusted for comorbidities at transplantation (more likely to be more frequent in older patients) in current study.…”
Section: Discussioncontrasting
confidence: 93%
“…This study also identified poor risk cytogenetics, being in second versus in first CR, and conditioning with low-dose TBI-based RIC as being associated with worse LFS or OS, confirming previous reports. 18,31,32 Finally, our study demonstrated higher mortality in patients above 56 years of age at transplantation in comparison with younger patients, in contrast to what has been observed in a recent report from the CIBMTR analyzing data from 545 patients with AML given RIC allo-SCT, 18 perhaps because analyses were not adjusted for comorbidities at transplantation (more likely to be more frequent in older patients) in current study.…”
Section: Discussioncontrasting
confidence: 93%
“…Another strategy used to prevent AML relapse after alemtuzumab-based RIC has been based on the pre-emptive administration of azacitidine which can likely favor the GVT effect without excessive GVHD. 36,37 Besides the impact of in vivo T-cell depletion on outcomes, this study also confirmed the negative impact of poor risk cytogenetics, 23,38,39 of being transplanted with a female donor in case of male recipients, 40 and of being transplanted in low-activity centers 18,22 on OS and PFS, as previously observed by our group 18,22,38,41 and by other groups of investigators. 39,40 Further, in contrast to what was observed in a recent CIBMTR study, 39 current data suggest that older patient age at transplantation is associated with higher NRM translating to worse LFS and OS in multivariate analyses.…”
Section: Discussionsupporting
confidence: 77%
“…132 Reported relapse rates have exceeded 40 or 50% with low-intensity regimens 27 or high-risk disease characteristics. 120,133 The median interval to AML relapse after RIC SCT is short-3-7 months, 27,119,134,135 and the median survival following relapse is 3-6 months. 135,136 The EBMT identified three factors that predicted better survival after relapse-long interval from transplant to relapse, low percentage of BM blasts and absence of acute GvHD.…”
Section: Relapse After Ric Sctmentioning
confidence: 99%
“…115 The disease risk index for AML is calculated on the basis of the cytogenetic risk profile and disease status at the time of transplant, both previously shown to be independent predictors of relapse and survival. 17,19,29,103,[116][117][118][119][120] An important predictor in early RIC studies was the absence of CR at the time of transplant, which predicted relapse and poor survival. 19,29,118,119 A detailed discussion of emerging data on disease characteristics, such as cytogenetic and molecular abnormalities is beyond the scope of this review.…”
Section: Predictors Of Outcome and Personalized Approachesmentioning
confidence: 99%